SYMBOLS IN JRAI PEOPLE’S LIFE-CYCLE RITUALS ACROSS VIETNAM’S CENTRAL HIGHLANDS - Phuong, THM (Proceeding of the International Conference on Arts and Humanities, 2023)
The Jrai ethnic group is the largest in the Central Highlands and has the tenth largest population of Vietnam’s 54 ethnic groups so studying Jrai culture, which emphasizes life cycle rituals and their symbols is a meaningful subject full of fascinating insight in to Central Highlands culture. Using qualitative data from ethnographic interviews and participant observation in three villages: Plei Oi, Greo Pet and Ia Glai districts, Chu Se and Phu Thien districts, and applying Clifford Greezt and Victor Turner’s symbolism theory, the paper describes, analyzes, and interprets the symbolic meaning in the Jrai life-cycle rituals. The study’s findings imply that everyday objects are turned into symbolic objects, supporting the community’s moral values in ritual context. For example, the midwife chews ginger and blows into the child’s ear, a practice known as " birth ritual". In order to mature into an adult, a youngster is enduring tooth - sharpening ritual. In the wedding ceremony, a couple exchange bracelets each other as a symbol of their lifelong love. To bid farewell to the deceased without regrets, bang the gong anti-clockwise around the corpse’s body. The symbolic framework of the life-cycle ritual has been preserved over time, conveying the ideals and identity of the Jrai ethnic group. The study’s findings contribute to explain why the Vietnamese government’s efforts to preserve ethnic cultures.